(untitled) (Global Media Journal - German Edition, 2012)
Hallin and Mancini’s book Comparing Media Systems has been hailed as a seminal work sparking several attempts at applying both the models and theoretical framework to media systems around the world. The following essay discusses important considerations on taking this framework beyond the confines of the Western world.